2014
DOI: 10.1080/14615517.2014.913761
|View full text |Cite
|
Sign up to set email alerts
|

Climate-change mitigation in Canadian environmental impact assessments

Abstract: Environmental impact assessments (EIAs) are still developing approaches to address the issue of climate change. The aim of the study is to examine how recent EIAs in Canada have approached the issue of greenhouse gas (GHG) emissions when evaluating each individual project's contribution to and impact significance on climate change. Twelve EIAs performed under national legislation in Canada were analyzed. Canada developed approaches to GHG emissions more than a decade ago, and it is now common to assess the emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…267 A review of Canada's practice revealed conditions ranging from the use of best technologies, to the adoption of a detailed GHG emissions management plan. 268 Less directly, in anticipation to CA, the proponents of large projects are likely to adopt alternatives which reduce GHG emissions, for instance by using the latest technology available when economically feasible. There is also some evidence that innovative conditions imposed as the result of a CA can promote new ideas which are then endorsed by lawmakers and imposed as a matter of general policy to all similar activities.…”
Section: Effects On the Final Decisionsmentioning
confidence: 99%
“…267 A review of Canada's practice revealed conditions ranging from the use of best technologies, to the adoption of a detailed GHG emissions management plan. 268 Less directly, in anticipation to CA, the proponents of large projects are likely to adopt alternatives which reduce GHG emissions, for instance by using the latest technology available when economically feasible. There is also some evidence that innovative conditions imposed as the result of a CA can promote new ideas which are then endorsed by lawmakers and imposed as a matter of general policy to all similar activities.…”
Section: Effects On the Final Decisionsmentioning
confidence: 99%
“…Notwithstanding the considerable legacy of research on Arctic climate change, we found very little Arctic EA research focused specifically on climate change and how, through EA, the impacts of climate change on Arctic development potential and the impacts of Arctic development on climate change can be best addressed. Although recent literature has focused on climate change mitigation in EA (Burdge, 2008;Byer et al, 2012), specifically project-based assessment and mitigation of greenhouse gas emissions (Sok et al, 2011;Ohsawa and Duinker, 2014), the implications for the EA process, and for those Arctic development sectors subject to EA, remain unexplored. Climate change will inevitably impose new demands on EA, but EA may also function as an essential tool for addressing the challenges to new and expanded development under changing climatic conditions.…”
Section: Adapting Ea To Climate Changementioning
confidence: 99%
“…Relatedly, clearly defined, criteria-based terminology should be developed in place of relativistic or value-based descriptors such as "minor," "temporary," "reasonable," "acceptably mitigated," or "significant." Heretofore, such terms have been used wantonly and diversely within and between project-level EAs (Murray et al 2018;Ohsawa and Duinker 2014), and my research findings suggest that their use as "empty signifiers" (Brown 2016) obscures meaning while simultaneously invoking frames and rationalizations that perform an argumentative function. Additionally, the weight afforded to particular values and effects in EA recommendations and decision-making is problematically opaque.…”
Section: Implications and Recommendations For Policy And Practicementioning
confidence: 98%
“…For example, there is still no scientifically-based metric or other specification regarding what constitutes a finding of "significance," despite the widely acknowledged central importance of the concept to EA practice (in addition to its widely inconsistent application) (Ohsawa and Duinker 2014). Likewise, there are still no clear resolutions to the problematic ambiguity of "relevance," or what can be justified "in the circumstances," or of broad powers of Ministers and agency officials to select and scope the factors under assessment (IAA, 22(2)).…”
Section: Implications and Recommendations For Policy And Practicementioning
confidence: 99%